2016. TaqMan Multiplex PCR of a Seven-Gene Host Biomarker to Discriminate Bacterial from Viral Infections. (26th November 2018) - Nie, Wensheng; Rawling, David; Eshoo, Mark; Khatri, Purvesh; Romanowsky, Jonathan; Liesenfeld, Oliver; Sweeney, Timothy
Abstract: Background: Acute infections are among the most frequent diagnoses in outpatient care settings. Early, accurate and rapid differentiation between viral and bacterial infections is critical to guide the choice of antimicrobial treatment, improve patient outcome, and to ensure antimicrobial stewardship. Current microbiological offerings rely on direct pathogen detection, which is limited by insufficient accuracy. Recently, host response-based molecular diagnostics have been considered as a novel alternative or complimentary approach. We have previously developed and validated a seven-gene signature set (higher in viral infections ( IFI27, JUP, and LAX1 ) and higher in bacterial infection ( HK3, TNIP1, GPAA1, and CTSB ) that accurately discriminated between viral and bacterial infections (in six validation cohorts, summary ROC AUC of 0.91 (95% CI, 0.82–0.96). We here describe the development of a rapid multiplex HostDx™ Fever, a seven-gene host response biomarker PCR assay that discriminates bacterial from viral infections. Methods: To translate the microarray-derived gene set into a rapid and easy to use assay to be run on an automated PCR instrument, TaqMan ® assays were designed, multiplexed and optimized for each of the seven targets. Data were then compared with NanoString ® and an ultrafast qPCR platform, respectively. Results: Seven TaqMan assays were divided into two multiplex reactions, one 5-plex and one 4-plex. KPNA6 was included as housekeeping control in each of the two multiplexes. Ten clinical samples from healthy subjects (3) or patients with confirmed viral (4) or bacterial (3) infections were tested in parallel on three platforms: regular qPCR, an ultrafast qPCR and NanoString platform. We found a high degree of concordance with R > 0.95 between TaqMan and NanoString platforms, and R > 0.94 between TaqMan and the ultrafast qPCR platform. Ultrafast qPCR results were obtained in 12 minutes. Conclusion: The discovered seven-gene set was validated and allows for robust discrimination between bacterial and viral infections. Multiplexing permits are more cost-effective method of testing. As a rapid test, HostDx™ Fever could assist in improved decision making for outpatients with suspected acute infections. Disclosures: W. Nie, Inflammatix Inc.: Employee, Salary. D. Rawling, Inflammatix Inc.: Employee, Salary. M. Eshoo, Inflammatix Inc.: Employee, Salary. P. Khatri, Inflammatix Inc.: Board Member, Equity. J. Romanowsky, Inflammatix Inc.: Employee, Salary. O. Liesenfeld, Inflammatix Inc.: Employee, Salary. T. Sweeney, Inflammatix Inc.: Employee, Salary.